Business strategy formulation: Case study of culinary SMEs - Nugrahaningtyas, Adham Aji; Triono, Sunu Puguh Hayu (Edelweiss Applied Science and Technology, 2025)
Small and Medium Enterprises (SMEs), which serve as vital pillars of the Indonesian economy, are currently facing significant challenges from macroeconomic pressures such as inflation and diminished consumer purchasing power. This study addresses the issue of declining profitability experienced by a culinary SME, Pecel Saestu, through determining the most effective competitive strategy to ensure its sustainability and growth in an uncertain economic climate. The novelty of this research lies in its application of a comprehensive, structured, multi-stage strategy formulation framework to a real-world SME case study. Employing a qualitative methodology, the study gathered data through in-depth interviews with management, a competitor, and customers, which was subsequently analyzed using a suite of tools including the EFE, IFE, IE, SWOT, and QSPM matrices. Empirical findings reveal a strong internal position (IFE score: 3.080) juxtaposed with a moderate response to significant external threats (EFE score: 2.655), placing the company in the 'grow and build' category. The QSPM analysis identified product development as the superior strategy (Total Attractiveness Score: 5.448). This research concludes that Pecel Saestu should introduce a tiered product portfolio featuring a 'Signature' (traditional) line and a 'Fusion' (lifestyle) line. This approach leverages the company's core R&D strengths to capture new market segments and improve profit margins.